AN INVESTIGATION INTO JAPINE PLATINUM PHOTOGRAPHS: WILLIAM WILLIS'S PROPRIETARY PAPER. Issue 4 (November 2015) - Clarke, Matthew L.; Mccabe, Constance; Maines, Christopher A.; Centeno, Silvia A.; Barro, Lisa; Vila, Anna
Abstract : Analyses of two samples of the commercial platinum photographic paper "Japine" revealed that this trade-name product was sold with a range of surface properties from matte to glossy. An in-depth examination of an unprocessed glossy Japine sample showed a chemically modified surface resulting from parchmentization by treatment with sulfuric acid. This treatment results in a thin film of amorphous cellulose on the printing surface, altering its visual appearance and wet strength. Photographers selected this paper due to its aesthetic qualities. However, such papers have never been characterized and are essentially unknown to modern-day scholars who may mistake them as prints with thin binder layers, such as albumen or gelatin. Indeed, the approach to conservation of these photographs may differ from one designed for a traditional platinum print. The parchmentized Japine paper was criticized for its tendency to crack, one characteristic that may have implications for its handling and conservation treatment today.